An Errors of Class VIII Junior High School Students in Solving Mathematical Communication Problems Based on the Newman Procedure - Anggraini, Linda; Wulandari, Shinta; R, Nurmala (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Mastery of mathematical communication is the primary capital in solving mathematical troubles. Mathematical communication abilities assist students in handing over thought or answers to a mathematical trouble in the form of oral, written, and image. The studies objective is to discover student mistakes in solving mathematical communication troubles. The form of research is descriptive qualitative so that the researcher is the principle instrument. Technical facts analysis on this research is descriptive qualitative statistics evaluation approach of Miles and Huberman model with ranges of facts discount, records presentation, conclusion drawing and verification. The records reduction level ambitions to pick, recognition, discard needless facts and simplify uncooked records from the outcomes of pupil errors analysis. The studies subjects have been students of class VIII A SMP Negeri 2 Tanjung Palas Utara. The studies confirmed that the students did now not make studying errors however made errors in knowledge, reworking, processing skill, and solving mathematical verbal exchange issues.
Keywords: Mathematical Communication; Newman Method; Student Error